2022
DOI: 10.1155/2022/1706716
|View full text |Cite|
|
Sign up to set email alerts
|

Network Pharmacology-Based Analysis on Lonicera japonica for Chronic Osteomyelitis Treatment

Abstract: Ethnopharmacological Relevance. Lonicera japonica (LJP) is a broadly used traditional Chinese medication treatment for chronic osteomyelitis (COM). But, the main antiosteomyelitis compounds and functional targets of LJP are still unclear. Aim of the Study. To screen LJP drug targets and active compounds in COM treatment. Materials and Methods. Active compounds of LJP were examined established on the analysis platform, Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. DrugBank identified drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…According to the ADME theory, oral bioavailability (OB) refers to the rate and degree of absorption of the active ingredient or active group of an oral drug into systemic circulation. [ 30 ] A higher OB value generally indicates better drug-like properties (DL) for biologically active drug molecules. Based on the literature, eligible chemical components were screened as active components with OB ≥ 30% and DL ≥ 0.18.…”
Section: Methodsmentioning
confidence: 99%
“…According to the ADME theory, oral bioavailability (OB) refers to the rate and degree of absorption of the active ingredient or active group of an oral drug into systemic circulation. [ 30 ] A higher OB value generally indicates better drug-like properties (DL) for biologically active drug molecules. Based on the literature, eligible chemical components were screened as active components with OB ≥ 30% and DL ≥ 0.18.…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%